Upaya meningkatkan pemahaman dan hasil belajar siswa terhadap unsur-unsur cerita/dongeng melalui media audio visual pada siswa kelas IV di SD Negeri I Mipiran - Eko Wahyuni (Jurnal Kualita Pendidikan, 2020)
This research was conducted to improve understanding and student learning outcomes through classroom action research using audio-visual media. This research was conducted in class IV SD Negeri 1 Mipiran with a total of 22 students consisting of 11 male students and 11 female students. This study aims to use audio-visual media in Indonesian language learning, as an effort to improve students' understanding and learning outcomes about the elements of stories/fairy tales. This research is focused on utilizing the use of audio-visual media in learning with the hope that students will be more active in participating in learning so that understanding and student learning outcomes will increase. In addition, to improve teacher performance to be more professional in managing, so as to produce more interesting and meaningful learning. The results showed an increase in both learning outcomes and student activeness in learning. Student learning outcomes showed an increase as follows: Before the improvement of the class average score of 62.5 and after the improvement had increased to 69, the class average increased by 6.5. Then it rose again to 76.8 with the class average score increased by 7.8. So it can be concluded that learning Indonesian about the elements of fairy tales through the use of audio-visual media can improve student understanding and learning outcomes.